2016
DOI: 10.4314/tjpr.v15i4.16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a root extract gel from <i>Urtica dioica</i> (Urticaceae) as analgesic and anti-inflammatory therapy in rheumatoid arthritis in mice

Abstract: Purpose: To develop and characterize an herbal gel prepared from methanol root extract of Urtica dioica (Urticaceae) (Stinging nettle) for the treatment of arthritis in mice.Methods: A methanol root extract from Urtica dioica was prepared, and a gel was then prepared using Carbopol 934. The prepared gel was subjected to various physical tests (color, appearance, pH, texture, viscosity)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Urtica dioica (UD) is a widespread herb that belongs to the family Urticaceae and the genus Urtica (Badirzadeh et al 2020). Various pharmacological activities such as anti-inflammatory (Liao et al 2016), anticancer (Mohammadi et al 2017), antirheumatic (Riehemann et al 1999), cardiovascular (Saleem et al 2002), antiaging, and antioxidant (Bourgeois et al 2016) have been reported from this tree. The predominant flavonoids, including quercetin, 3-rutinosides, kaempferol, isoquercitrin, astragalin, rutin, isorhamnetin, and 3-glycosides were recorded from this plant (Figure 3) (Martínez-Aledo et al 2020).…”
Section: Urtica Dioicamentioning
confidence: 99%
“…Urtica dioica (UD) is a widespread herb that belongs to the family Urticaceae and the genus Urtica (Badirzadeh et al 2020). Various pharmacological activities such as anti-inflammatory (Liao et al 2016), anticancer (Mohammadi et al 2017), antirheumatic (Riehemann et al 1999), cardiovascular (Saleem et al 2002), antiaging, and antioxidant (Bourgeois et al 2016) have been reported from this tree. The predominant flavonoids, including quercetin, 3-rutinosides, kaempferol, isoquercitrin, astragalin, rutin, isorhamnetin, and 3-glycosides were recorded from this plant (Figure 3) (Martínez-Aledo et al 2020).…”
Section: Urtica Dioicamentioning
confidence: 99%
“… 2011 ; Liao et al. 2016 ). Despite its diversity and economic importance, our understanding of the many relationships within Urticaceae remains limited, with morphological homogeneity and phenotypic plasticity impeding morphological classification (Wu et al.…”
mentioning
confidence: 99%
“…Urticaceae is a large cosmopolitan family containing over 2000 species, which is notable for its high ecological diversity. Furthermore, medicinal usage of some taxa within Urticaceae is being increasingly studied (Chen et al 2003;Luo et al 2011;Liao et al 2016). Despite its diversity and economic importance, our understanding of the many relationships within Urticaceae remains limited, with morphological homogeneity and phenotypic plasticity impeding morphological classification (Wu et al 2015).…”
mentioning
confidence: 99%
“…Aerial part Amino acid-Aspartic acid, Threonine, Serine and Alanine 19 Chlorigenic acid 57 Anti-inflammatory 57 Hepato-protective, Antioxidant 63 Antirheumatoid arthritis 65 Root lignans -(+)-neoolivil, (-)-secoisolariciresinol, dehydrodiconiferyl alcohol, isolariciresinol, pinoresinol, and 3, 4-divanillyl-tetrahydro-furan 22 Antiprostatic hyperplasic 54 …”
Section: Urtica Urensmentioning
confidence: 99%
“…Antiarthritic Activity: Methanolic extract of the root of Urtica dioica has been used as a remedy for rheumatoid arthritis due to suppression of cytokine production 65 .…”
Section: Antioxidantmentioning
confidence: 99%